PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP CSR PERUSAHAAN PERTAMBANGAN TERDAFTAR DI BEI PERIODE 2017-2019 - Vincent Yonathan Kinsey; Urip Santoso (Business Administration Department - Universitas Katolik Parahyangan, 2021)
Social responsibility is a contribution from a company as a corporate responsibility to the community. Public limited companies that are listed on the Indonesia Stock Exchange (BEI) should disclose their social responsibilities. Especially in the industries that are related to natural resource processing, it is required in Law number 4 of 2009 concerning mineral and coal mining Article 108 (1) to carry out social responsibility. Disclosure of information consists of mandatory and voluntary disclosures. Financial information is a mandatory disclosure. This disclosure of company financial information triggers this research that focuses on the characteristics of the company. This research focuses on the effect of firm characteristics with dimension of company size, board member size, and managerial ownership. This research was conducted on mining companies in Indonesia listed on the BEI for the period 2017–2019. The results prove that the total assets of the company, the size of the board of directors, and managerial ownership have a partial influence on the implementation, and disclosure of social responsibility. Based on the simultaneous testing, the size of the company, the size of the board of directors, and managerial ownership have a significant effect on the disclosure of social responsibility.